(untitled) (CIPEEX, 2023)
This analyzes the energy plan adopted by Brazil in the context of global climate challenges, with an emphasis on the goal of achieving Net Zero by 2050, which involves balancing greenhouse gas (GHG) emissions. The expansion of renewable energy sources and the reduction of GHG emissions in Brazil’s energy matrix are crucial to achieving this goal. In 2020, the National Energy Plan 2050 was launched, with the goal of transforming the Brazilian energy matrix into a fully renewable one, as well as becoming a net energy exporter, producing enough to meet its needs and exporting the surplus. The Brazilian energy transition faces challenges, including the expansion of renewable sources such as hydropower, wind, and solar, as well as the improvement of infrastructure and logistics to support the growth of these sources. Moreover, sources such as solar and wind energy, due to their variability, require adaptations to ensure a reliable energy supply. In summary, the National Energy Plan 2050 represents a comprehensive and strategic guide for Brazil’s energy transition, providing clear goals and strategies to promote technological growth and the use of renewable and non-renewable sources. It is a crucial step towards a sustainable energy matrix and contributes to global efforts to combat climate change.